Avaliação de ésteres destilados do biodiesel como aditivos ao diesel - Silva, Fernanda Lima Rei Ramos e (2022)
The objective of the present work is to investigate the effect of adding light and heavy biodiesel distillates to diesel on spark ignition engine performance and exhaust emissions, as well as on fuel characterization. All tests were carried out using commercial diesel (DC) as base fuel and its 10% (v/v) blends with the biodiesel distillates (BL10 and BP10) and biodiesel itself (B10). Characterization tests were run in accordance with the corresponding ASTM methods. Results showed that all formulations fit within the established standards for commercialization, in accordance with ANP resolution Nº 50. Engine performance investigation was conducted on a diesel engine, varying wheel power from 0 kW to 1,2 kW while rotation remains constant at 3600 rpm, in order to generate brake specific fuel consumption (BSFC) curves. Results showed engine efficiency improvement when running on the formulations compared to commercial diesel, with BSFC lower by 18,88% at load condition of 0 kW and by 13,27% at load condition of 1,2 kW (B10 compared to DC). Exhaust emissions data was captured by a Testo gas analyser for detection of CO, CO2, NOx. The ester additives promoted more complete combustion of the fuel, leading to reduction in CO emissions by up to 30,9% (BP10 compared to DC at 0,6 kW). CO2 and NOx emissions were increased up to 24,7% (B10 compared to DC at 0,9 kW) and 80,2% (B10 compared to DC at 0,9 kW), respectively. Thus, it is possible to conclude that the additives were effective in promoting a cleaner burning of the fuel, without compromising engine efficiency.